Mitral valve repair for ischemic mitral regurgitation - Mohebali, Jahan; Chen, Frederick Y. (Annals of Cardiothoracic Surgery, 2015)
Mitral valve repair for ischemic mitral valve regurgitation remains controversial. In moderate mitral regurgitation (MR), controversy exists whether revascularization alone will be adequate to restore native valve geometry or whether intervention on the valve (repair) should be performed concomitantly. When MR is severe, the need for valve intervention is not disputed. Rather, the controversy is whether repair versus replacement should be undertaken. In contrast to degenerative or myxomatous disease that directly affects leaflet integrity and morphology, ischemic FMR results from a distortion and dilation of native ventricular geometry that normally supports normal leaflet coaptation. To address this, the first and most crucial step in successful valve repair is placement of an undersized, complete remodeling annuloplasty ring to restore the annulus to its native geometry. The following article outlines the steps for repair of ischemic mitral regurgitation.